Views on the Utilization of Non-Halal Assets - Firmansyah Firmansyah; Aas Nurasyiah; Suci Aprilliani Utami; Ripan Hermawan; Muhammad Kamal Muzakki; Romi Hardiansyah (Review of Islamic Economics and Finance, 2022)
Purpose – This paper aims not to legalize the practice of unlawful muamalah transactions, but the real purpose is what to do if someone has already made unlawful transactions and generates wealth from the practice of unlawful muamalah transactions, what is the solution to repentance in Islam, so as not to repeat muamalah transactions illegal in the future.Methodology - This paper uses a qualitative method in the form of library research. Literature study is a technique of collecting data by examining books, literatures, articles and research reports that have to do with the problem being solved. Thus, this study will limit its activities only to library collection materials without conducting field researchFindings - The conclusion of this paper is that if the illicit assets resulting from transactions that are not mutually pleased and the whereabouts of the transaction partners are known, it must be returned or their consent is requested, while if the whereabouts of the transaction partners are not known, the assets are donated to the poor on behalf of the owner of the goods/money legitimate.Keywords: Non-Halal Assets, Muamalah Haram, Utilization of Non-Halal Assets, Repentance